2003
DOI: 10.1074/jbc.m306767200
|View full text |Cite
|
Sign up to set email alerts
|

Lithostathine Quadruple-helical Filaments Form Proteinase K-resistant Deposits in Creutzfeldt-Jakob Disease

Abstract: Autocatalytic cleavage of lithostathine leads to the formation of quadruple-helical fibrils (QHF-litho) that are present in Alzheimer's disease. Here we show that such fibrils also occur in Creutzfeldt-Jakob and Gerstmann-Strä ussler-Scheinker diseases, where they form protease-K-resistant deposits and co-localize with amyloid plaques formed from prion protein. Lithostathine does not appear to change its native-like, globular structure during fibril formation. However, we obtained evidence that a cluster of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
51
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 47 publications
4
51
0
2
Order By: Relevance
“…protease-K-resistant fibrils [181] that deposit in the brain of patients with Creutzfeld-Jakob disease [182] and Gertsmann-Straüssler-Scheinker syndrome [183], especially during the very early stages. figure 14) and (2) fusion of a growing protofibril to a pre-existing profofibril (light-blue arrows in figure 14).…”
Section: Protein Self-assembly Processesmentioning
confidence: 99%
“…protease-K-resistant fibrils [181] that deposit in the brain of patients with Creutzfeld-Jakob disease [182] and Gertsmann-Straüssler-Scheinker syndrome [183], especially during the very early stages. figure 14) and (2) fusion of a growing protofibril to a pre-existing profofibril (light-blue arrows in figure 14).…”
Section: Protein Self-assembly Processesmentioning
confidence: 99%
“…On the one hand, amyloid formation may occur readily from peptides as short as 5 residues, where formation of structure before assembly is rather unlikely given the short length of the peptides (12). On the other hand, a number of observations have indicated that fibrillar aggregates may originate from the assembly of globular protein molecules in their native or native-like state (13,14). The yeast prion Ure2p was shown to form fibrils that display birefringence upon Congo red binding and increased resistance to proteinase K treatment, typical of amyloid fibrils (15)(16)(17).…”
mentioning
confidence: 99%
“…Accordingly, x-ray fiber diffraction analysis has shown that the fibrils do not possess a cross-␤-structure (18). Similarly, lithostathine, a protein that forms both independent and colocalized deposits with amyloid ␤ plaques, neurofibrillary tangles, and PrP sc plaques, maintains its native content of secondary structure, although it aggregates into fibrillar structures (14). In this case the resulting proteinase K-resistant fibrils do not bind Congo red in addition to showing no cross-␤-structure (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They have been described as inhibitors of calcium carbonate crystal growth in vitro ( [1] and [2]), as growth factors ( [3] and [4]), as mitogens for pancreatic β-cells ( [5] and [6]), and as a motoneuron neurotrophic factor [7]. They have also been implicated in carcinogenesis ( [8]; [9] and [10]), in the improvement of diabetes in murine models ( [11] and [12]), and in neurodegenerative diseases ( [13] and [14]). …”
Section: Introductionmentioning
confidence: 99%